Constructing In2S3/CdS/N-rGO Hybrid Nanosheets via One-Pot Pyrolysis for Boosting and Stabilizing Visible Light-Driven Hydrogen Evolution - Minghao Zhang; Xiaoqun Wu; Xiaoyuan Liu; Huixin Li; Ying Wang; Debao Wang (Molecules, 2023)
The construction of hybrid junctions remains challenging for the rational design of visible light-driven photocatalysts. Herein, In2S3/CdS/N-rGO hybrid nanosheets were successfully prepared via a one-step pyrolysis method using deep eutectic solvents as precursors. Benefiting from the surfactant-free pyrolysis method, the obtained ultrathin hybrid nanosheets assemble into stable three-dimensional self-standing superstructures. The tremella-like structure of hybrid In2S3/N-rGO exhibits excellent photocatalytic hydrogen production performance. The hydrogen evolution rate is 10.9 mmol·g−1·h−1, which is greatly superior to CdS/N-rGO (3.7 mmol·g−1·h−1) and In2S3/N-rGO (2.6 mmol·g−1·h−1). This work provides more opportunities for the rational design and fabrication of hybrid ultrathin nanosheets for broad catalytic applications in sustainable energy and the environment.